The process of NATO enlargement in Europe - Gajić Dejan (Međunarodni Problemi)
The paper deals with the main aspects of NATO enlargement since its foundation in 1949. The author points to the basic criteria for NATO accession during the past sixty years. Special reference is given to the main issues concerning accession of new NATO members in the post-Cold War era. The author presents the Study of NATO Enlargement, a basic document that laid out rationales for enlargement. He also gives the key elements of European security and contemporary NATO-Russia relations.